0

[3*32+13*(-2)]+7[8-(4-9)]

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
[ 3 * 32+13 * ( -2) ] + 7 [ 8 - ( 4- 9) ] =

(96 -26) + 7 ( 8 +5) =

70  + 7*13= 70 + 91 = 161
Ralph L. | Algebra I, II, Visual Basic, Beginning C++ tutorAlgebra I, II, Visual Basic, Beginning C...
4.0 4.0 (1 lesson ratings) (1)
0
[96 - 26] + 7[8-(-5)]

70 + 7(13)

70 + 91 = 161
Jason T. | Jason Tutors Math & PhysicsJason Tutors Math & Physics
4.9 4.9 (152 lesson ratings) (152)
0
The key in this problem is to apply the order of operations correctly.

P
E
MD
AS

[3*32+13*(-2)] + 7[8-(4-9)]

Parentheses:  perform any operations within parentheses first

(4-9) = -5  -->   [3*32+13*(-2)] + 7[8-(-5)]

[8-(-5)] = 13  -->  [3*32+13*(-2)] + 7*13 = 3*32 + 13*(-2) + 7*13

Exponents: none in this problem

Multiplication and Division left to right:

3*32 = 96  --> 96 + 13*(-2) + 7*13

13*(-2) = -26  -->  96 + (-26) + 7*13

7*13 = 91  --> 96 + (-26) + 91

Addition and Subtraction left to right:

96 + (-26) = 70  -->  70 + 91 =161